UPAYA PEMERINTAH INDONESIA DALAM MENANGANI MASALAH IMIGRAN ILEGAL YANG MENUJU AUSTRALIA TAHUN 2012-2015 - Maulana, Ilham; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research describes the policy of Indonesia government in anticipation illegal migration case destinate to Australia in 2012-2015. Australia especially Christmast Island are one of most the dstination route for illegal migration from Afganistan, Pakistan, Suriah, Srilanka and Turkey. When imigrant came to Australia they will transit in Indonesia and this can make the threat for Indonesia security stability.The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze the policy of Indonesia government in anticipation illegal migration case destinate to Australia. The theories applied in this research are realism with the transnational concept by Barry Buzan.The conclusion of this research about the policy of Indonesia government in anticipation illegal migration case destinate to Australia are have done with some steps, likes Indonesia Government increase a controlling in border area by Indonesia Police, Imigration and Forein Ministry, Indonesia government has cooperation between Australia to anticipate the illegal imigration with dealling about Bali Process, Indonesia Government has cooperation with UNHCR dan IOM to anticipate the illegal imigration that transit in Indonesia.Key words: policy, anticipation, illegal and imigration